Developing historical technical basis for material and package classification and package test requirements of international transport safety regulations. (December 2013) - Pope, R.; Bajwa, C.; Malesys, P.; Zhao, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> In a companion PATRAM 2013 paper, C. Bajwa et al. provide an overview of international level efforts that began in 2010 to develop a comprehensive and detailed Technical Basis Document (TecBasDoc) to support the current International Atomic Energy Agency (IAEA) Transport Regulations (SSR-6, 2012) and future revisions thereto. The draft TecBasDoc that has so far resulted from efforts by a large number of IAEA staff and international experts exceeds 300 pages in length using, to the greatest extent possible, historical documents dating as far back as the 1950s as reference material. The intent is to capture, for those Member States new to transport and for future generations, the scientific and technical heritage of the several decades of development that has occurred in transport safety, preserving this knowledge for future reference. The latest effort, in December 2012, involved consultants to the IAEA adapting the draft to reflect guidance from the IAEA's Transport Safety Standards Committee and delving into the IAEA's archives searching out many long sought, older supporting documents. This paper elaborates on Chaps. 8–10 of the TecBasDoc, dealing with respectively Classification of Materials, Classification of Packages and Package Design and Testing. Chapter 8 elaborates on the many decisions resulting in an initial nine material classifications, which focused more on the physical and not the radioactive characteristics of the materials, to the current, significantly different classifications that focus more on the material's radioactive properties. Chapters 9 and 10 combine to provide extensive, detailed elaboration on why decisions were made concerning the various package classifications and the associated design, testing and acceptance requirements associated with each package type. Chapter 10 cites two extensive supporting appendices. These three chapters and two appendices currently cite and elaborate on >200 historical documents. Efforts are underway to make this extensive document base more complete and to make as many documents as possible available electronically. In this paper, each of these three drafted chapters and the two supportive appendices are overviewed, providing insight into key and typical findings that have been uncovered and incorporated into the draft document. The many experts who have contributed to the current draft are appropriately acknowledged.